Algorithmics of the knapsack type tasks - Pătcaş, Csaba; Ionescu, Klára (Teaching Mathematics and Computer Science, 2008)
We propose a new kind of approach of the teaching of knapsack type problems in the classroom. We will remind you the context of the general knapsack-task and we will classify it, including the two most popular task variants: the discrete and the continuous one. Once we briefly present the solving algorithm of the continuous variant, we will focus on the solving of the discrete task, and we will determine the complexity of the algorithms, looking for different optimizing possibilities. All these issues are presented in a useful way for highschool teachers, who are preparing students in order to participate in different programming contests.